Ecofuture pemberdayaan Ibu PKK Desa Loru Berbasis Zero Waste melalui pengelolaan Jagung - I Made Rio Dwijayanto; Inayah Salsabilah; Aning Pratiwi; Ferdi Arifin; Najwa Sarita M.N (Penerbit Widina, Widina Media Utama, 2025)
Corn production in Sigi Regency, Central Sulawesi, generates a large amount of agricultural waste in the form of corn cobs, husks, and silk. This condition prompted the EcoFuture-PKM PM community service program in Loru Village. The aim of this program is to improve the knowledge and skills of PKK women in processing corn waste based on the Zero Waste principle. With 15 PKK group members as the main partners, the activities took place over four months at the Loru Village Hall. A participatory descriptive approach was used, allowing participants to be involved in all stages of the program, from planning to evaluation. This method enabled the program to provide participants with practical knowledge and skills so that they could develop sustainable corn waste management practices. The results of the activity showed that participants gained a better understanding of waste management and learned how to make corn silk tea, herbal powder, aromatherapy candles, and corn husk crafts from cobs. The participants' response was very positive, with active participation and a desire to continue production on their own. Additionally, this program raises community awareness about environmental issues and offers opportunities to establish small businesses based on agricultural waste. The results of the activity show that the objectives of community service can be achieved by improving participants' skills and awareness of the Zero Waste principle in utilizing corn waste sustainably.ABSTRAKProduksi jagung di Kabupaten Sigi, Sulawesi Tengah menghasilkan limbah pertanian yang sangat besar berupa tongkol, kulit, dan rambut jagung. Kondisi ini mendorong program pengabdian EcoFuture-PKM PM di Desa Loru. Tujuan program ini adalah untuk meningkatkan pengetahuan dan keterampilan Ibu-Ibu PKK dalam pengolahan limbah jagung berdasarkan prinsip Zero Waste. Dengan mitra utama 15 peserta kelompok PKK, kegiatan berlangsung selama empat bulan di Balai Desa Loru. Dalam proses ini, pendekatan deskriptif partisipatif digunakan, yang memungkinkan peserta berpartisipasi dalam semua tahapan program, dari perencanaan hingga evaluasi. Metode ini memungkinkan program memberikan pemahaman dan keterampilan praktis kepada peserta sehingga mereka dapat membangun perilaku pengelolaan limbah jagung yang berkelanjutan. Hasil kegiatan menunjukkan bahwa peserta lebih memahami pengelolaan limbah dan belajar membuat teh rambut jagung, bedak herbal, lilin aromaterapi, dan kerajinan kulit jagung dari tongkol. Respon peserta sangat positif, dengan partisipasi aktif dan keinginan untuk melanjutkan produksi sendiri. Selain itu, program ini meningkatkan kesadaran masyarakat tentang masalah lingkungan dan menawarkan peluang untuk mendirikan usaha kecil berbasis limbah pertanian. Hasil kegiatan menunjukkan bahwa tujuan pengabdian dapat dicapai melalui peningkatan kemampuan peserta dan kesadaran tentang prinsip Zero Waste dalam memanfaatkan limbah jagung secara berkelanjutan.